2013
DOI: 10.5007/2175-7925.2013v26n2p105
|View full text |Cite
|
Sign up to set email alerts
|

Biology of Neoseiulus californicus feeding on two-spotted spider mite

Abstract: ResumoBiologia de Neoseiulus californicus alimentando-se de ácaro rajado. Tetranychus urticae (Koch) destaca-se por ser um ácaro polífago. Em morangueiro, esse ácaro desenvolve-se na face inferior das folhas, causando lesão significativa. Este estudo teve por objetivo conhecer as características biológicas de Neoseiulus californicus (McGregor), proveniente de plantas de morangueiro cultivado. O estudo iniciou-se com trinta ovos individualizados em arenas com diferentes estágios de T. urticae como alimento. A d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Neoseiulus californicus fed on T. ludeni, presented higher net reproductive rate (Escudero and Ferragut, 2005) than the net reproductive rate presented in this work. However, Toldi et al (2013) observed a similar result, when such predator was fed on T. urticae.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Neoseiulus californicus fed on T. ludeni, presented higher net reproductive rate (Escudero and Ferragut, 2005) than the net reproductive rate presented in this work. However, Toldi et al (2013) observed a similar result, when such predator was fed on T. urticae.…”
Section: Discussionsupporting
confidence: 64%
“…Escudero and Ferragut (2005) studied N. californicus fed on T. ludeni and obtained higher results. Toldi et al (2013) also obtained higher results when N. californicus was fed on T. urticae.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations